Behavior of Axially Loaded Stirrup Confinement Rectangular Concrete-Filled Steel Tubular Stub Columns - Jing Liu; Wen-jun Wang; Fa-xing Ding; Xin-fa Zeng; Zhe Tan; Yan Huang; Bao-quan Wang (Advances in Civil Engineering)
This article presents the experimental and finite element (FE) analyses of two conventional rectangular concrete-filled steel tubular (CFT) stub columns, two stiffened rectangular concrete-filled steel tubular (SCFT) stub columns, and two stirrup confinement rectangular concrete-filled steel tubular (CCFT) stub columns concentrically loaded in compression to failure. The influences of the ductility and ultimate bearing strength of these stub columns with stiffening ribs or spiral stirrup confinement were discussed. Abaqus was used to establish a 3D FE model and analyze the properties of CFT stub columns subjected to axial compression. The effect of the concrete core and rectangular steel tube under loop stirrup confinement was discussed. Analytical results showed that spiral stirrup confinement can availably retard the local bucking of the rectangular steel pipe, and the effect of the spiral stirrup confinement was stronger than that of stiffeners. The DI values of SCFT and CCFT were 21.9% and 31.9% larger than those of CFT, respectively. The ultimate capacity values of SCFT and CCFT were 10.2% and 18% larger than those of CFT, respectively. The ductility and ultimate bearing strength of the specimens improved effectively under spiral stirrup confinement, and the ductility of the CCFT columns was preferable to that of the SCFT columns.